Comprehensive Analysis of the Effectiveness of Omnichannel Marketing Strategy in Increasing Sales Optimization in Companies - Sutomo Sutomo (International Journal of Management Science and Information Technology, 2023)
This study aims to evaluate the effectiveness of omnichannel marketing strategies in optimizing a company's sales performance. By integrating online and offline sales channels, omnichannel strategies provide a seamless customer experience. This study uses a quantitative approach with a descriptive-analytical method to analyze the relationship between omnichannel strategy and sales performance. A sample of 150 retail companies was selected through purposive sampling, ensuring that only companies implementing a comprehensive omnichannel strategy were included. Data collection was conducted through structured surveys and secondary sources, where respondents rated the strategy's effectiveness using a 5-point Likert scale. The results showed a significant increase in sales performance, with an average increase of 18% in the surveyed companies. In addition, customer satisfaction and operational efficiency were found to act as moderating variables in the relationship between omnichannel strategies and sales performance. This study concludes that omnichannel marketing strategies effectively increase sales and customer satisfaction, with recommendations for further research and practice focused on improving inventory management and technology integration.